(untitled) (Ágora Journal, 2021)
The present text aims at establishing certain levels of understanding about the fight against leprosy in two states of the Brazilian Federation: Ceará and Espírito Santo, between the 1920s and 1940s. We indicate that the creation of leprosariums in Ceará (Canafístula) in 1928 and in Espírito Santo (Itanhenga) in 1937 enabled effective actions to combat this disease which was reckoned at the time as hideous. We assert that the charitable actions of the society in Ceará were very important in the implementation of compulsory isolation with little state intervention; as of Espírito Santo, the action of the instituted powers in the implementation of public policies in the fight against the disease was fundamental. We also notice there, however, the importance of society through the more affluent strata, who working together with the State, sought alternatives to support the leprosy sanitation project financially. Although the public policy of the State regarding leprosy reached the states of the Federation in a uniform manner, we detect similarities but also differences in how leprosariums were created and how they worked in Ceará and Espírito Santo. We used, as sources, periodicals from Ceará and Espírito Santo, administrative reports from the management of the leprosariums, reports by Presidents of Provinces, mail received by the management of the leprosariums, Leprosy Service activity report.